(untitled) (Uzbek Scholar Journal, 2022)
In the article today, the interactive method of pedagogical technology in learning English and its place in educational systems, the most important aspect of this method is the term interactive, its meaning, this method. Games focused on the development of the student’s thinking, the place and role in the development of the student’s creative talent, memory and attention are highlighted.